1994
DOI: 10.1016/s0022-5347(17)32645-9
|View full text |Cite
|
Sign up to set email alerts
|

Some Pre- and Postjunctional Effects of Castration in Rabbit Isolated Corpus Cavernosum and Urethra

Abstract: Pre- and postjunctional effects of castration were investigated in isolated corpus cavernosum (CC) and prostatic and preprostatic urethral preparations obtained from rabbits that had been castrated surgically 14 days before investigation. Preparations obtained from untreated animals were used as controls. Castration did not change the relaxing effects of SIN-1 (NO donor) or papaverine in CC preparations contracted by noradrenaline (NA). Electrical field stimulation of CC preparations contracted by NA or endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…11,12 Holmquist et al reported that castration increase the relaxation of corpus cavernosum strips to electrical stimulation through decrease in the neuronal release of NA. 13 Meanwhile, Baba reported that tissue strips from intact rabbits showed a greater degree of contraction than those of castrated animals, suggesting changes in the adrenergic pathway in response to androgen deprivation. 14 Castration reduces NANC fibers in rat model; 15 however, these fibers are thought to be decreased in the castrated model, 13 suggesting differences in the response to androgens among species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Holmquist et al reported that castration increase the relaxation of corpus cavernosum strips to electrical stimulation through decrease in the neuronal release of NA. 13 Meanwhile, Baba reported that tissue strips from intact rabbits showed a greater degree of contraction than those of castrated animals, suggesting changes in the adrenergic pathway in response to androgen deprivation. 14 Castration reduces NANC fibers in rat model; 15 however, these fibers are thought to be decreased in the castrated model, 13 suggesting differences in the response to androgens among species.…”
Section: Discussionmentioning
confidence: 99%
“…13 Meanwhile, Baba reported that tissue strips from intact rabbits showed a greater degree of contraction than those of castrated animals, suggesting changes in the adrenergic pathway in response to androgen deprivation. 14 Castration reduces NANC fibers in rat model; 15 however, these fibers are thought to be decreased in the castrated model, 13 suggesting differences in the response to androgens among species. Recently, Traish et al reported that castration reduces intracavernosal pressure and expression of a1-adrenergic receptor while increasing phosphodiesterase type 5 activity.…”
Section: Discussionmentioning
confidence: 99%
“…53 Upon castration, electrically evoked relaxations of the smooth muscle of the prostatic urethra were decreased and this effect was ascribed to an impaired ability of the smooth muscle to respond to relaxant agents. 54 The effects of testosterone can be partially explained by the fact that NO production is androgen dependent in the urinary tract. NOS in an earlier study had appeared to be androgen dependent in the urogenital tract of the rat.…”
Section: Sex Hormonesmentioning
confidence: 99%
“…31,32 In rabbits, with strips of cavernosal tissue precontracted with a-adrenergic agonists, electrical field stimulation caused a greater degree of relaxation in strips from castrate than from intact animals. 33 The contraction in response to norepinephrine may also be hormonally dependent, with strips from intact rabbits showing a greater degree of contraction than tissues from castrates in response to the same concentration of the agonist. 34 Relaxation in response to field stimulation was greater in castrated than in intact animals, although relaxation in response to NO donor drugs was not different in the two groups, suggesting that basal NOS may be adequate to mediate the erectile response.…”
Section: Role Of Ischemic Factorsmentioning
confidence: 99%